Microeconomic Adjustment Hazards and Aggregate Dynamics - Caballero, R. J.; Engel, E. M. R. A. (Quarterly Journal of Economics, 1993)
The basic premise of this paper is that understanding aggregate dynamics requires considering that agents are heterogeneous and that they do not adjust continuously to the shocks they perceive. We provide a general characterization of lumpy behavior at the microeconomic level in terms of an adjustment-hazard function, which relates the probability that a unit adjusts to the deviation of its state variable from its moving target. We characterize rich, cross-sectionally dependent aggregate dynamics generated by nonconstant hazards. We present an example based on U. S. manufacturing employment and job flows, and find that increasinghazard models outperform constant-hazard-partial-adjustment models in describing aggregate employment dynamics.